Propagande et « contre-propagande » en Irlande pendant la Première Guerre mondiale - Jérôme aan de Wiel (Revue LISA)
The First World War caused a major propaganda battle in Ireland between, on the one hand, the constitutional Nationalist Party, led by John Redmond, and the British authorities who were both in favour of the war and voluntary recruitment, and on the other hand, Sinn Féin, opposition nationalists and also a few Catholic clergymen who were against the British war effort in the country, deeming that the home rule crisis had not been dealt with in a satisfactory way. This article aims at shedding light on the confrontation between the two sides. It seems that the British authorities were rather disorganised in their various propaganda campaigns, while Sinn Fein pursued an energetic and sometimes vitriolic anti-war campaign. One of the themes used by the latter was France’s pre-war anti-clerical policy. This article will consider the extent to which propaganda and “counter-propaganda” influenced voluntary recruitment in Ireland where conscription was not imposed.